2019
DOI: 10.3389/fgene.2019.01017
|View full text |Cite
|
Sign up to set email alerts
|

From Genetics to Epigenetics, Roles of Epigenetics in Inflammatory Bowel Disease

Abstract: Inflammatory bowel disease (IBD) is a destructive, recurrent, and heterogeneous disease. Its detailed pathogenesis is still unclear, although available evidence supports that IBD is caused by a complex interplay between genetic predispositions, environmental factors, and aberrant immune responses. Recent breakthroughs with regard to its genetics have offered valuable insights into the sophisticated genetic basis, but the identified genetic factors only explain a small part of overall disease variance. It is be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
85
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(86 citation statements)
references
References 127 publications
(218 reference statements)
0
85
0
1
Order By: Relevance
“…The identification of markers for the diagnosis of IBD is of utmost importance, and DNA methylation and miRNAs (microRNA) are special biomarkers for diagnosis at the molecular level. Indeed, studies have shown a strong sensitivity, specificity, and precision of these markers in the diagnosis of IBD [ 106 ].…”
Section: Epigenetics and Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of markers for the diagnosis of IBD is of utmost importance, and DNA methylation and miRNAs (microRNA) are special biomarkers for diagnosis at the molecular level. Indeed, studies have shown a strong sensitivity, specificity, and precision of these markers in the diagnosis of IBD [ 106 ].…”
Section: Epigenetics and Ibdmentioning
confidence: 99%
“…Additionally, epigenetic markers related to immunoregulation, intestinal epithelial barrier, and autophagy are differently expressed among IBD and healthy controls, and between UC and CD patients as well. Moreover, miRNAs may be used as biomarkers for disease assessment in the future, as they are more convenient than endoscopy and biopsies, mainly for patients with active disease [ 106 ]. MiRNA are a class of small non-coding RNA (17–22 nucleotides) that regulates gene expression post-transcriptionally.…”
Section: Epigenetics and Ibdmentioning
confidence: 99%
“…IBD arises as a result of inappropriate immune response to intestinal commensal organisms in individuals with genetic predisposition and consequently causes inflammation and intestinal ulcers [1] ,. In addition, IBD has a complex pathogenesis and many factors such as dysbiosis, oxidative stress, and epigenetics that may also be involved in disease pathogenesis [2] , [3] , [4] . Ulcerative colitis (UC) and Crohn's diseases (CD) are known as two main forms of IBD.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of markers for the diagnosis of IBD is of utmost importance, and DNA methylation and miRNAs are special biomarkers for diagnosis at the molecular level. Indeed, studies have shown a strong sensitivity, specificity, and precision of these markers in the diagnosis of IBD [16].…”
Section: Epigenetics and Ibdmentioning
confidence: 99%
“…Indeed, epigenetics may explain how environment and genetics might be involved in the development, progression, pathogenicity, and response to treatments. Also, epigenetic markers related to immunoregulation, intestinal epithelial barrier, and autophagy are differently expressed among IBD and healthy controls, and between UC and CD patients as well, and miRNAs (microRNA) may be used as biomarkers for disease assessment in the future, as they are more convenient than endoscopy and biopsies, mainly for patients with active disease [16].…”
Section: Introductionmentioning
confidence: 99%